Learning from a crisis: a qualitative study of the impact on mothers’ emotional wellbeing of changes to maternity care during the COVID-19 pandemic in England, using the National Maternity Survey 2020 - McLeish, J; Harrison, S; Quigley, M; Alderdice, F (BioMed Central, 2022)
Background Pregnancy and the postnatal period can be times of psychosocial stress and insecurity, but high quality maternity care and social support can help mothers cope with stress and feel more secure. The COVID-19 pandemic and associated social and economic disruption increased rates of antenatal and postnatal stress, anxiety and depression, and also had profound impacts on the organisation of maternity services in England.